(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article presents the socio-economic importance of training middle-level personnel based on the needs of the private sector in a market economy, as well as existing challenges and solutions. The results of the work carried out on the training of middle-level personnel based on the needs of employers in the private sector were analyzed, and recommendations were developed to improve the processes of training competitive middle-level personnel in the vocational education system.